Sofosbuvir-Based Therapy for Genotype 4 HCV Recurrence Post-Liver Transplant Treatment-Experienced Patients - A. Ajlan; A. Al-Jedai; H. Elsiesy; D. Alkortas; W. Al-Hamoudi; R. Alarieh; M. Al-Sebayel; D. Broering; F. Aba Alkhail (Canadian Journal of Gastroenterology and Hepatology)
Background and Aim. This is an open label prospective cohort study conducted at a tertiary care hospital. The primary endpoint is SVR12 in patients treated with sofosbuvir-based therapy in post-liver transplant patients with genotype 4 HCV recurrence. Methodology. Thirty-six treatment-experienced liver transplant patients with HCV recurrence received sofosbuvir and ribavirin ± peginterferon. Results. We report here safety and efficacy data on 36 patients who completed the follow-up period. Mean age was 56 years, and the cohort included 24 males and one patient had cirrhosis. Mean baseline HCV RNA was 6.2 log10 IU/mL. The majority of patients had ≥ stage 2 fibrosis. Twenty-eight patients were treated with pegylated interferon plus ribavirin in addition to sofosbuvir for 12 weeks and the remaining were treated with sofosbuvir plus ribavirin only for 24 weeks. By week 4, only four (11.1%) patients had detectable HCV RNA. Of the 36 patients, 2 (5.5%) relapsed and one died (2.75%). Conclusion. Our results suggest that sofosbuvir + ribavirin ± pegylated interferon can be utilized successfully to treat liver transplant patients with HCV recurrence.